(untitled) (Baghdad Science Journal, 2025)
Twenty bacterial isolates were identified as Staphylococcus aureus collected from wounds and catheters related infections. A capsulated S. aureus isolate was chosen after performing serum soft agar test, for this study Neutropenic mice were challenged with capsulated S. aureus ,and the effect of G-CSF with or without moxifloxacin was studied. The results indicated that the addition of G-CSF to moxifloxacin therapy have a synergistic effect in the killing of the bacteria, while when each G-CSF and moxifloxacin were used seperately have a similar effect on bacterial killing. It was found that the moxifloxacin has the same activity as G_CSF but is less costly than the latter one.